Analisis Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Produk Kecap Sedaap di Pasir Pengaraian - Melani Bella Saputri; Heffi Christya Rahayu; Andi Afrizal (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of Product Quality and Brand Image on Purchasing Decisions of Sedaap Soy Sauce Products in Pasir Pengaraian. The research method used is a quantitative approach with multiple linear regression analysis techniques assisted by the SPSS program. The population in this study are consumers who buy and consume Sedaap Soy Sauce products in the Pasir Pengaraian area, both those who have become regular customers and those who are trying the product for the first time. The research sample was taken using stratified random sampling technique with the Slovin formula, so that 100 respondents were obtained. Data were collected through questionnaires distributed to consumers of Kecap Sedaap who were respondents to the study. The results showed that the T-count value for product quality reached 2,903 and for brand image was 3,931, both of which were greater than the T-table of 1,984, which indicated a positive and significant influence on purchasing decisions. Simultaneously, the F test showed an F-count value of 144,788, greater than the F-table of 2.70, which indicated that product quality and brand image had a positive and significant influence together on purchasing decisions. The average Respondent Achievement Rate (TCR) for purchasing decisions was 77.81%, which indicated a good category. Thus, this study concluded that both product quality and brand image significantly increased purchasing decisions for Kecap Sedaap products in Pasir Pengaraian.